Intimate partner violence among prenatal care attendees amidst the COVID‐19 crisis: The incidence in Ethiopia. Issue 1 (19th January 2021) - Teshome, Abel; Gudu, Wondimu; Bekele, Delayehu; Asfaw, Mariamawit; Enyew, Ruhama; Compton, Sarah D.
Abstract: Objective: To assess the incidence and predictors of intimate partner violence (IPV) during pregnancy amidst the coronavirus disease 2019 pandemic. Methods: This cross‐sectional study was conducted at the prenatal care clinic of St. Paul's Hospital Millennium Medical College (SPHMMC), Addis Ababa, Ethiopia, among pregnant women from 31 August to 2 November 2020. Participants were interviewed using Open Data Kit. Logistic regression was used to assess predictors. Results: Among the 464 pregnant women, 33 (7.1%) reported IPV during pregnancy, and among these 24 (72.7%) reported emotional violence, 16 (48.5%) reported sexual violence, and 10 (30.3%) reported physical violence. Among the study participants, only 8 (1.7%) were screened for IPV. IPV was reported 3.27 times more often by women who reported that their partner chewed Khat compared with those women whose partner did not (adjusted odds ratio [aOR] 3.27; 95% confidence interval [CI] 1.45–7.38), and 1.52 times more often women who reported that their partner drank alcohol compared with those women whose partner did not (aOR 1.52; 95% CI 1.01–2.28). Conclusion: Very few women were screened for IPV. Partners drinking alcohol and chewing Khat are significantly positively associated with IPV during pregnancy. IPV screening should be included in the national management protocol of obstetric cases of Ethiopia. Abstract : Very few women were screened for intimate partner violence during pregnancy, a finding that has implications for policy moving forward.